The Production of Coating Film with Sweet Potato Starch and Carboxymethylcellulose from Water Hyacinth on Storage Life Extension of Mango (Mangifera indica L.) - Theamdee, Pawinee; Walmuntri, Nattharikar (Trends in Sciences, 2024)
The objective of this research was to study the production of coating films with sweet potato starch (SPS) and carboxymethyl cellulose (CMC) from water hyacinth and to study the effect of the coating on the storage life extension of mangoes. The coating film was prepared by dissolving sweet potato starch in water at a concentration of 5 % w/v and adding CMC from water hyacinth at 5 different concentrations: 0, 5, 10, 15, and 20 % based on the weight of the starch. Glycerol was added as a plasticizer at 20 % of the weight of the starch solution. The mixture was then dried at 65 °C for 18 h. The study found that the thickness of the film decreased with higher concentrations of CMC from water hyacinth. The water activity (aw) ranged from 0.35 to 0.42, and the solubility and water vapor permeability of the film decreased with increasing CMC concentration. In the degradation study, it was observed that the films could biodegrade from 42 to 100 % for 8 weeks, with degradation rates decreasing as the amount of CMC from water hyacinth increased. Coating Mango with 10 % w/w CMC helped delay weight loss, skin color changes, and extended the shelf life of mango for up to 18 days at room temperature (28 ± 2 °C, 65 ± 2 % RH), compared to the control group with a shelf life of 12 days. These results indicate that films made from SPS/CMC from water hyacinth, with glycerol as the plasticizer, can effectively be used for preserving fruits and creating biodegradable films. HIGHLIGHTS The coating film of sweet potato starch (SPS) and Carboxymethylcellulose (CMC) from Water Hyacinth was prepared The effect of adding different CMC concentrations in SPS films was investigated This coating film is cost-effective and biodegradable The coating film of SPS and CMC from water hyacinth enhances the shelf-life of perishable fruit GRAPHICAL ABSTRACT